2017
DOI: 10.3390/ijms18081722
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Rich Fibrin Facilitates Rabbit Meniscal Repair by Promoting Meniscocytes Proliferation, Migration, and Extracellular Matrix Synthesis

Abstract: Although platelet-rich fibrin (PRF) has been used in clinical practice for some time, to date, few studies reveal its role as a bioactive scaffold in facilitating meniscal repair. Here, the positive anabolic effects of PRF on meniscocytes harvested from the primary culture of a rabbit meniscus were revealed. The rabbit meniscocytes were cultured with different concentrations of PRF-conditioned medium, and were evaluated for their ability to stimulate cell migration, proliferation, and extracellular matrix form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 48 publications
(74 reference statements)
3
35
0
Order By: Relevance
“…The bioactivity and chemotactic effect of PRF on cell recruitment and migration is crucial to the development of our one-stage, culture-free, and scaffold-based approach. In previous studies, the efficacy of PRF chemotaxis at both the cellular and tissue levels has been investigated, showing that PRF can promote rabbit meniscocyte and chondrocyte migration, similar to that seen when using platelet-rich plasma [25,27,32]. These results were also consistent with studies performed on rabbit and goat models [6,33].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The bioactivity and chemotactic effect of PRF on cell recruitment and migration is crucial to the development of our one-stage, culture-free, and scaffold-based approach. In previous studies, the efficacy of PRF chemotaxis at both the cellular and tissue levels has been investigated, showing that PRF can promote rabbit meniscocyte and chondrocyte migration, similar to that seen when using platelet-rich plasma [25,27,32]. These results were also consistent with studies performed on rabbit and goat models [6,33].…”
Section: Discussionsupporting
confidence: 79%
“…No additional activation steps are required, and the release of growth factors from PRF can be steadily sustained [24]. The effects of PRF in facilitating rabbit meniscal and cartilage repairs have been documented in [6,[25][26][27] however, the relatively small joint size, thin cartilage layer, and great potential for intrinsic healing have limited the translational value for this one-stage cartilage treatment method.…”
Section: Introductionmentioning
confidence: 99%
“…Positive anabolic effects of PRF on meniscocytes harvested from the primary culture of a rabbit meniscus were reported in vitro in terms of cell migration, proliferation, and extracellular matrix formation (58). In addition, efficacy of PRF on facilitation of meniscal repair was shown in a rabbit model of meniscal defects with significantly improved quality of meniscal healing noted in the PRF-augmented suture vs. non-suture or suture-only groups (58). Hence, the potential utility of PRF-based therapeutic approach has been suggested in augmenting the healing of meniscal injuries in clinical practice (58).…”
Section: Meniscal Repairmentioning
confidence: 99%
“…Platelet-rich fibrin (PRF) is also being used in clinical practice [ 66 – 68 ]. Wong et al showed that PRF enhanced cellular migration and promoted both meniscocyte proliferation and meniscocyte ECM secretion in vitro [ 69 ]. PRF has also been proven to promote meniscal repair in a rabbit meniscal defect model.…”
Section: Cell-free Strategies For Meniscus Repair and Regenerationmentioning
confidence: 99%
“…They showed that the application of 2.5%–30% PRP or 10% HS resulted in meniscal cell recruitment in both groups [ 91 ]. Similarly, Wong et al showed that platelet-rich fibrin (PRF) could promote cellular migration and enhance both the proliferation and ECM synthesis of meniscocytes [ 69 ]. PRF is an autogenous fibrin-based biomaterial.…”
Section: Recruitment Factors For Endogenous Cell Homing In Meniscamentioning
confidence: 99%